Implementing a Resource-Based Relative Value Scale Fee Schedule for Physician Services An Assessment of Policy Options for the California Workers' Compensation Program - Wynn, Barbara O. (RAND Corporation, 2013)
RAND researchers used 2011 medical data to examine the impact of implementing a resource-based relative value scale to pay for physician services under California's workers' compensation system. Current allowances under the Official Medical Fee Schedule are approximately 116 percent of Medicare-allowed amounts and, by law, will transition to no more than 120 percent of Medicare payment amounts over four years. This report details the researchers' findings.